Glyco-Steroidal Amphiphiles (GSAs) for membrane protein structural study - Ehsan,M; Wang,H; Katsube,S; Munk,CF; Du,Y; Youn,T; Yoon,S; Byrne,B; Loland,CJ; Guan,L; Kobilka,BK; Chae,PS (ChemBioChem: a European journal of chemical biology, 2022)
Integral membrane proteins pose considerable challenges to high resolution structural analysis. Maintaining membrane proteins in their native state during protein isolation is essential for structural study of these bio-macromolecules. Detergents are the most commonly used amphiphilic compounds for stabilizing membrane proteins in solution outside a lipid bilayer. We previously introduced a glyco-diosgenin (GDN) detergent that was shown to be highly effective at stabilizing a wide range of membrane proteins. This steroidal detergent has additionally gained attention due to its compatibility with membrane protein structure study via cryo-EM. However, synthetic inconvenience limits widespread use of GDN in membrane protein study. To improve its synthetic accessibility and to further enhance detergent efficacy for protein stabilization, we designed a new class of glyco-steroid-based detergents using three steroid units: cholestanol, cholesterol and diosgenin. These new detergents were efficiently prepared and showed marked efficacy for protein stabilization in evaluation with a few model membrane proteins including two G protein-coupled receptors. Some new agents were not only superior to a gold standard detergent, DDM (n-dodecyl-β-d-maltoside), but were also more effective than the original GDN at preserving protein integrity long term. These agents represent valuable alternatives to GDN, and are likely to facilitate structural determination of challenging membrane proteins.